The POTENTIAL OF Syzigium aromaticum L. TO CONTROL LEAF SPOT DISEASE (Cercospora capsici) IN CAYENNE PEPPER (Capsicum frutescens L.) - Yenny Muliani; Dwi Susanto; Ida Adviany; Neng Tita Nursinta; Debby Ustari (SEAMEO BIOTROP, 2025)
Article Highlights: - In preliminary lab tests, clove leaf extract clearly slowed C. capsici growth.- Field trials assessed its potential to reduce leaf spot disease in cayenne pepper.- Applying concentrations above 15 g/L tended to lower the observed disease intensity.- The same concentration range was also linked to an increase in leaf number.- However, low field disease incidence limited detectable yield responses.Abstract:Cayenne pepper (Capsicum frutescens L.) is a spice plant that has good prospects for development in Indonesia because of its high market demand. There are several problems in increasing the production of this crop, one of which the plant diseases. One of the main diseases in cayenne pepper is leaf spot disease caused by the fungus Cercospora capsici (Heald & F.A. Wolf). Chemical pesticides can effectively control the disease but they have negative effects on the environments. Clove tree (Syzigium aromaticum L.) is usually cultivated for its dried clove buds that can be used for many other purposes. Besides, because of their contents, the leaves of clove tree have a potential to reduce the intensity of leaf spot disease. Therefore, the aims of the study were (1) to determine the effects of clove leaf extract on reducing the intensity of Cercospora capsici (Heald & F.A. Wolf) in cayenne pepper, and (2) to determine the effective concentration of the extract in reducing the intensity of the disease. The experiment used a randomized block design (RBD) with 5 treatments and 5 replications, namely: A = control (water only), B = 10 g clove leaf extract/L water, C = 15 g clove leaf extract/L water, D = 20 g clove leaf extract/L water, and E = 25 g clove leaf extract/L water. The results showed that the applications of leaf extract of Syzigium aromaticum L. could reduce the intensity of the leaf spot disease caused by Cercospora capsici, but the applications had no effect on the yield of the cayenne pepper. The ineffectiveness of treatments on the yield was deduced due to the lowness of the intensities of the disease in all treatments including the control.